How 'smart' are we with smart technology: comparison of water ATMs in Nairobi and Delhi. Issue 10 (29th September 2022) - Sarkar, Anindita
Abstract: New forms of decentralized water infrastructure with digital projects driven by private investment are being introduced in low-income urban neighborhoods in the global south with the aim of increasing the coverage of affordable and safe water. These 'smart' water-vending machines are gaining popularity to meet water demand in growing cities as they are low-cost, transparent, revenue generating and replicable. However, field evidence from Nairobi and Delhi shows that similar technologies implemented to solve similar problems in different geographical and social settings can have completely different outcomes. Smart technologies can offer better outcomes when the implementing agencies and policy makers make smart choices about implementation, setting aside utopian hype. HIGHLIGHTS: Water ATMs in cities can be successful if they are socially and economically viable. Location of water ATMs is central to its success as it determines the scale of water sale. Water ATMs are not intrinsically pro- or anti-poor, and it can become pro-poor only with sound management. Their replicability cannot ignore the power and relevance of context because cities are complex and can enable, disrupt and resist the use of technologies.